LncRNA PVT1 promotes tumorigenesis of glioblastoma by recruiting COPS5 to deubiquitinate and stabilize TRIM24 - Tao Lv; Yichao Jin; Yifeng Miao; Tianqi Xu; Feng Jia; Haizhong Feng; Xiaohua Zhang (Elsevier, 2022)
LncRNA PVT1 has been implicated in numerous pathophysiological processes and diseases, especially cancers. However, the role and mechanism of PVT1 in the tumorigenesis of glioblastoma remain unclear. We investigated the alteration of PVT1 and its key functions in glioblastoma. PVT1 was upregulated and associated with poor prognosis in glioblastoma. We demonstrated that PVT1 silencing suppressed cell proliferation, colony formation, and orthotopic xenograft tumor growth. Mechanistic investigations found that PVT1 interacted with TRIM24 directly and increased its protein stability. PVT1 recruited COPS5 to deubiquitinate TRIM24; reciprocally, PVT1 depletion impaired the interaction between COPS5 and TRIM24, resulting in decreased expression of TRIM24. PVT1, TRIM24, and COPS5 coordinately contributed to the activation of STAT3 signaling and malignant phenotype of glioblastoma. Collectively, this study elucidates the essential role of PVT1 in the tumorigenesis of glioblastoma, which provides candidacy therapeutic target for glioblastoma treatment.